Drone-based development of SIPEJAR statistical for education course content packages - Pahrany, Andi Daniah; Suwarman, Ramdhan Fazrianto; Aeli, Lita Wulandari; Solikhin, Mukhammad (Jurnal Kajian Pembelajaran Matematika, 2024)
Learning Management System (LMS) is an innovation in the learning process that allows online learning to be more effective and efficient. Like many other higher education institutions, Universitas Negeri Malang provides opportunities for innovation and easy access to knowledge by utilizing an LMS called the Sistem Pengelolaan Pembelajaran (SIPEJAR). SIPEJAR is an open-source system that can be modified according to the user's needs and desires. The aim of this research is to develop SIPEJAR content packages by using the ADDIE model for statistics for education courses with drone-based learning. SIPEJAR development products include lesson plans, textbooks, and SIPEJAR content packages for 16 meetings. Drone-based development is focused on developing explanatory videos, presentation slides, and student interaction with learning materials. The finding results indicated that the drone-based development of SIPEJAR content packages is valid with an average score of 3.77 out of 4, practical with an average score of 4.19 out of 5, and quite effective with classical completeness percentage obtained was 60% with an average score of 74.63. This means that drone-based SIPEJAR content packages have been well developed, even though they can be improved further. Our research findings indicated that the E-LKPD is valid with a percentage of 91.00%, practical with a percentage of 89.05%, and effective with a classical learning completeness percentage of 82.76%